Microwave assisted acid hydrolysis for bioethanol fuel production from sago pith waste. (1st March 2019) - Thangavelu, Saravana Kannan; Rajkumar, T.; Pandi, Dinesh Kumar; Ahmed, Abu Saleh; Ani, Farid Nasir
Highlights: Microwave acid hydrolysis was carried out using H2 SO4 and HCl for SPW. A maximum of 88% glucose yield and 3.1 g ethanol per 10 g SPW was obtained. Energy consumption to produce 1 g glucose and 1 g bioethanol fuel was calculated. A minimum of 31. 77 kJ was used to produce 1 g bioethanol fuel from SPW. Abstract: Microwave assisted acid hydrolysis (H2 SO4 and HCl with >0.5 mol/L) to produce bioethanol from sago pith waste (SPW) was studied. The energy consumption for microwave hydrolysis at different energy inputs and acid concentration were calculated. The overall energy consumption for bioethanol fuel production from SPW was assessed. A maximum of 88% glucose yield and 80% ethanol yield (3.1 g ethanol per 10 g SPW) were obtained using 1.0 mol/L H2 SO4 . Microwave hydrolysis using 1.0 mol/L H2 SO4 consumed the minimum energy of 8.1 kJ to produce 1 g glucose from SPW when energy input was fixed at 54 kJ (900 W for 1 min). In general, 1 g glucose can produce 16 kJ. The overall energy consumption for fuel grade bioethanol production from SPW was 31.77 kJ per g ethanol, which was slightly higher than the lower heating values of ethanol (26.74 kJ/g ethanol).